Assessment of thyroid lesions using fine-needle aspiration cytology in accordance with The Bethesda System and its histopathological correlation - Mishra, Himachal; Alexander, Manika; Bommanahalli, Basavaraj (Journal of Pathology of Nepal, 2023)
Background: Fine Needle Aspiration Cytology is a first-line diagnostic technique that provides an accurate and precise diagnosis for assessing thyroid abnormalities. This study was conducted to analyze the cytology smears of thyroid lesions using The Bethesda system of reporting thyroid cytology and to correlate the cytological findings with histopathology diagnosis to determine the diagnostic accuracy of FNAC. Materials and methods: A prospective cross-sectional study was carried out. FNAC of thyroid lesions of 203 patients were examined and reported as per the Bethesda system for reporting thyroid cytopathology. Of these, 33 patients underwent surgery, whose histopathological findings were compared and correlated with respective cytopathological diagnoses. The IBM SPSS (Statistical Package for the Social Sciences) software version 27 was used for data analysis. Results: Among 203 cases evaluated, there were 11 Non-diagnostic (Category I) cases, 171 benign (Category II) cases, 4 cases of atypia of undetermined significance (Category III), 7 were suspicious for Follicular Neoplasm (Category IV), 2 were suspicious for malignancy (Category V) and 8 were malignant (Category VI). Out of 203 patients, only 33 patients underwent surgery, of whom 26 (78.79%) were benign and 7 (21.21%) were malignant on histopathology. The corresponding values for sensitivity, specificity, and diagnostic precision of FNAC were 71.42%, 100%, and 93.93% respectively, while positive and negative predictive values were determined as 100% and 92.85% respectively. Conclusions: The study shows that thyroid tumors can be successfully categorized and reported cytologically as per The Bethesda system.